Single-step synthesis of hyperbranched, luminescent Mn2+-doped ZnSe1−xSx nanocrystals using dichalcogenide precursors. Issue 28 (27th June 2016) - Yazdanparast, Mohammad S.; Webb, Matthew T.; McLaurin, Emily J.
Abstract : Taking advantage of dichalcogenide precursors, a simple, single-step heat-up method for obtaining Mn 2+ -doped ZnSe1− x S x nanocrystals (NCs) is presented. Abstract : Taking advantage of dichalcogenide precursors, a simple, single-step heat-up method for obtaining Mn 2+ -doped ZnSe1− x S x nanocrystals (NCs) is presented. Tuning the ratios of diselendide and disulfide precursors results in alloys with varying shape, size and composition. When diphenyldiselenide (Ph2 Se2 ) is used, highly branched networks of small NCs form. Dimethydisulfide (Me2 S2 ) induces formation of larger NCs with less branching. Mixtures of the two exhibit branching proportional to the amount of Ph2 Se2 vs. Me2 S2, allowing formation of a series of branched Mn 2+ -doped NCs. Interestingly, these NCs exhibit photoluminescence (PL) characteristic of Mn 2+, despite the large number of defects and unusual shapes they possess. This demonstrates Mn 2+ can be successfully doped into NCs with several degrees of branching, in which it acts as an efficient radiative trap. Addition of thiol to the NCs led to a large enhancement in the Mn 2+ PL. In organic solution, the sensitivity to thiol varied with the degree of NC branching, with hyperbranching NCs giving the most sensitive response. After transfer to aqueous solution, the Mn 2+ PL of the hyperbranched NCs increased dramatically in response to μM concentrations of dithiothreitol (DTT).